Glucose-6 phosphate dehydrogenase deficiency and newborn screening - Bhaumik, Samapika; Patel, Suprava; Padhi, Phalguni (International Journal of Research in Medical Sciences, 2020)
Glucose-6 phosphate dehydrogenase (G6PD) deficiency is an X-linked recessive disorder causing breakdown of RBCs. It affects over 400 million people, making it the most common enzymopathy in the world. It leads to hereditary predisposition to hemolysis. In India, various study results reveal an incidence ranging from 2 to 27.9% in different communities. It is known globally for its genetic and phenotypic heterogeneity with 13 biochemically characterized variants have been reported from India, G6PD Mediterranean being the most common. It is mostly asymptomatic but certain triggers like infections, some medications, chemicals, stress or food may precipitate hemolysis. It is important to understand the epidemiology and distribution pattern in India because of its higher prevalence in tribal population who are more prone for malaria. Irrational use of drugs for malaria treatment has attributed high mortality especially neonatal mortality, in this community. Newborn screening is one of the best options to diagnose the case at neonatal age. Implementation of newborn screening would aid in identifying the genetic disorders in order to provide comprehensive care along with parental counselling to reduce the complications associated with it.